Establishment of a circular polymerase extension reaction–based reverse genetics system for porcine reproductive and respiratory syndrome virus - Akiha Inoue; Inori Goda; Isshu Kojima; Mana Esaki; Kosuke Okuya; Makoto Ozawa (Veterinary Microbiology, 2026)

A refined framework for acute dietary exposure assessment of agricultural chemical residues in composite foods: A case study using salmon consumption data - Kosuke Nakamura; Takahiro Inoue; Takashi Kiuchi; Tatsuya Koyama; Ikuo Hirono; Kumiko Ogawa; Hiroshi Akiyama (Food and Humanity, 2026)

Association between deletions in the preS1/2 region of the hepatitis B virus genome and persistently abnormal ALT levels in patients with chronic hepatitis B treated with nucleos(t)ide analogs - Yurina Sato; Kotaro Doi; Jun Inoue; Masashi Ninomiya; Mio Tsuruoka; Kosuke Sato; Masazumi Onuki; Satoko Sawahashi; Keishi Ouchi; Kengo Watanabe; Hirofumi Niitsuma; Atsushi Masamune (Archives of Virology, 2026)
Patients with chronic hepatitis B (CHB) are at risk of developing hepatocellular carcinoma (HCC) during treatment with nucleos(t)ide analogs (NAs). Several factors, including abnormal ALT levels during NA treatment, are associated with HCC risk; however, the mechanisms of ALT abnormalities remain unknown. Here, deletions in the preS1/2 region of the hepatitis B virus (HBV) genome were evaluated in the context of persistent ALT abnormalities after NA treatment. Out of the 198 patients with CHB who had been treated with NAs, 40 who had been treated with entecavir, tenofovir disoproxil fumarate, or tenofovir alafenamide fumarate as the first-line therapy and from whom serum samples had been collected before NA treatment were selected for analysis of the infecting virus. Total DNA was extracted from the samples and subjected to nested PCR to detect deletions in the preS1/2 region of the HBV genome. Patients for whom deletions were found in ≥ 40% of the amplicons were classified as the "high-del" group, and the others were the "low-del" group. The preS1/2 region was amplified from 39 (97.5%) of the 40 samples, and a deletion was found in 19 of these patients (48.7%). The cumulative incidence of HCC was found to be significantly higher in the high-del group than in the low-del group (25% vs. 7% at 2 years, P = 0.021). The high-del group also had significantly higher ALT levels than the low-del group after 1 year of NA treatment (35 vs. 26 U/L, P = 0.020). In summary, patients with CHB with frequent preS1/2 deletions showed higher ALT levels after NA treatment and a higher risk of developing HCC.

Trend analysis of time series variations in the marine environments and size-fractionated chlorophyll a in the coastal areas of eastern Hokkaido, southwestern Okhotsk Sea - Akihiro Shiomoto; Kosuke Inoue; Takeshi Okunishi (Journal of Marine Systems, 2025)

Reliable intraoperative diagnostic methods for PCNSL: utility of combining intraoperative immunohistochemistry, cytology, and flow cytometry in achieving optimal treatment - Akihiro Inoue; Yukihiro Miyazaki; Hideaki Watanabe; Masahiro Nishikawa; Kosuke Kusakabe; Takanori Ohnishi; Mashio Taniwaki; Takatsugu Honda; Takuya Kondo; Shingo Kinnami; Eiji Katayama; Seiji Shigekawa; et al. (Acta Neurologica Belgica, 2025)

Defatted microalgae Haematococcus pluvialis: A sustainable source for gold recovery - Jhapindra Adhikari; Gehui Pang; Shintaro Morisada; Hidetaka Kawakita; Keisuke Ohto; Katsutoshi Inoue; Mikihide Demura; Shuuji Maeda; Kosuke Nakamizo (Journal of Environmental Chemical Engineering, 2024)

Systematic comparison of Mg K-edge XANES spectra of magnesium-bearing clay minerals and magnesium silicate hydrates: A promising tool for identifying magnesium silicate hydrate in natural samples - Kosuke Inoue; Yuto Nishiki; Keisuke Fukushi; Reo Suma; Tsutomu Sato; Hiroshi Sakuma; Kenji Tamura; Shingo Yokoyama; Misato Shimbashi; Tomoyuki Mizukami; Kensuke Unami; Yohei Noji; et al. (Applied Clay Science, 2023)

Per- and polyfluoroalkyl substances and sleep health in U.S. adults, NHANES 2005–2014 - Pengfei Guo; Zhihao Jin; Giselle Bellia; Jiajun Luo; Kosuke Inoue; Krystal J. Godri Pollitt; Nicole C. Deziel; Zeyan Liew (Environmental Research, 2023)

Correction to: Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

Air Pollution and Adverse Pregnancy and Birth Outcomes: Mediation Analysis Using Metabolomic Profiles - Kosuke Inoue; Qi Yan; Onyebuchi A. Arah; Kimberly Paul; Douglas I. Walker; Dean P. Jones; Beate Ritz (Current Environmental Health Reports, 2020)

Buffering effects of job resources on the association of overtime work hours with psychological distress in Japanese white-collar workers - Ayako Hino; Akiomi Inoue; Norito Kawakami; Kanami Tsuno; Kimiko Tomioka; Mayuko Nakanishi; Kosuke Mafune; Hisanori Hiro (International Archives of Occupational and Environmental Health, 2015)